Phospholipid binding properties and functional characterization of a sea urchin phospholipase Cdelta in urchin and mouse eggs. - Coward, K; Owen, H; Tunwell, R; Swann, K; Parrington, J (2007)
We recently identified a novel phospholipase Cdelta isoform, PLC-deltasu, in sea urchin gametes, whose precise functional role during fertilization and early embryogenesis remains unknown. Here, we characterized the binding of the PLC-deltasu PH domain to different phosphatidylinositol (PI) phospholipids and studied changes in its localization during fertilization. The PLC-deltasu PH domain bound most strongly to PI(3,4)P(2) and PI(3,5)P(2) phospholipids, in contrast to the PLCdelta1 PH domain which bound predominantly to PI(4,5)P(2). A green fluorescent protein tagged PLC-deltasu PH domain localized to the plasma membrane and its localization increased at fertilization and following addition of a Ca(2+) ionophore. However, recombinant PLC-deltasu failed to cause Ca(2+) signals like those seen at fertilization, in mouse and sea urchin eggs. Our findings suggest that PLC-deltasu is unlikely to be directly involved in the process of egg activation but may play a role in mediating extracellular signals transmitted via the PI 3'-kinase pathway.